The effect of blocked and random practice on the underhand throw ability in male boccia athletes with cerebral palsy - Doewes, R. I.; Elumalai, G.; Azmi, S. H. (Journal of Physical Education and Sport, 2022)
The purpose of this study was to determine the effects of blocked and random practice on underhand throw ability in boccia and to determine the best practice for improving this skill. Eighteen male athletes of Indonesian boccia with cerebral palsy participated in this study. The subjects were 18 male athletes of boccia in Indonesia with cerebral palsy with a mean age of 23.11±1.02 years, height of 160.22±4.94 cm, and weight of 65.26±2.23 kg. The subjects underwent an initial underhand throw test to be divided into two intervention groups, i.e. blocked practice and random practice (each group consisted of 9 athletes), and then underwent an intervention for 8 weeks. Data were collected by using an underhand throw test using the Boccia Ball Throwing Accuracy Test Instrument. T-test was used for data analysis to test the effect of practice on the ability to underhand throw in boccia. The paired t test showed that there was an effect of blocked practice and random practice on the underhand throw ability of male boccia athletes with cerebral palsy (p = 0.000 for blocked practice and p = 0.002 for random practice). Independent t test showed that blocked practice had a better effect than random practice for improving the underhand throw ability of male boccia athletes with cerebral palsy (p = 0.006), as shown by percentage increase in blocked practice by 118.333% compared to that in random practice of 57.895%. Thus, blocked practice and random practice have a statistically significant effect on underhand throw ability in boccia, and blocked practice has a better effect than random practice.